Quality Of Egg Rendang By Using Different Types Of Eggs - Affriadi, Rhiska Septyani; Gusnita, Wiwik (Universitas Negeri Padang, 2022)
Randang talua is Randang made from eggs. This Randang is unique compared to other types of Randang, which is flat, similar to crackers. In this study, the types of eggs used to make rendang talua were divided into two, namely chicken eggs and duck eggs. This research is an experiment with organoleptic test. This research was conducted 3 times with 5 limited panelists. The data obtained were analyzed using the T test (t test). The results showed that the average value of the quality of the two randang was almost the same. The average value of the quality of rendang with the use of chicken eggs and duck eggs is 3,27 and 3,47; the color of the talua chips are 3.33 and 3.27; the color of randang bran 3.00 and 3.13; the aroma of randang is 3.47 and 3.53; the texture of the randang bran is 3.33 and 3.33; the texture of talua chips are 3.20 and 3.47; and the taste of randang talua, namely 3.53 and 3.67. Based on the t test, it was stated that there was no significant difference between randang talua and the use of chicken eggs and duck eggs for each quality tested.